Dexterity and technique in termite fishing by chimpanzees (Pan troglodytes troglodytes) in the Goualougo Triangle, Republic of Congo. Issue 1 (16th November 2020) - Osuna‐Mascaró, Antonio J.; Ortiz, Camila; Stolz, Caroline; Musgrave, Stephanie; Sanz, Crickette M.; Morgan, David B.; Fragaszy, Dorothy M.
Abstract: Although the phenomenon of termite fishing by chimpanzees ( Pan troglodytes ) has historical and theoretical importance for primatology, we still have a limited understanding of how chimpanzees accomplish this activity, and in particular, about details of skilled actions and the nature of individual variation in fishing techniques. We examined movements, hand positions, grips, and other details from remote video footage of seven adult and subadult female chimpanzees using plant probes to extract Macrotermes muelleri termites from epigeal nests. Six chimpanzees used exclusively one hand (left or right) to grip the probe during termite fishing. All chimpanzees used the same repertoire of actions to insert, adjust, and withdraw the probe but differed in the frequency of use of particular actions. Chimpanzees have been described as eating termites in two ways—directly from the probe or by sweeping them from the probe with one hand. We describe a third technique: sliding the probe between the digits of one stationary hand as the probe is extracted from the nest. The sliding technique requires complementary bimanual coordination (extracting with one hand and grasping lightly with the other, at the same time). We highlight the importance of actions with two hands—one gripping, one assisting—in termite fishing and discuss how probing techniques are correlated with performance. Additional research on digital function and on environmental, organismic, and task constraints will further reveal manual dexterity in termite fishing. Abstract : chimpanzee fishing termites using the sliding technique. Research Highlights: ‐ Using remote video footage from camera traps in Goualougo Triangle, Republic of Congo, we describe chimpanzees' manual actions, postures, and positions, and movements of the probe while they fished for termites in epigeal termite nests. ‐ Chimpanzees used diverse grips, with and without the thumb, and two hands—one gripping, one assisting—to handle the probe delicately and to move it precisely. ‐ We describe a new technique for recovering termites: sliding the probe between the digits of one stationary hand as the probe is extracted from the nest with the other hand, and a new action: oscillatory movements of the probe while it was inserted in the nest.